Litho-geochemical Characterizations of the Kourouba Gold Mineralization in the North East of the Republic of Guinea - CONTE, Mohamed Samuel Moriah; DIALLO, Moussa; KOUROUMA, Mory; TIMITE, Mohamed Lamine; Fofana, Mohamed; CAMARA, Mohamed; CAMARA, Djibril M’Mamy; KEITA, Alpha Yaya; ZOUMANIGUI, Akoi (International Journal of Scientific Research and Management (IJSRM), 2025)
The essentially gold resources of the countries of the West African sub-region are associated with the formations of the Proterozoic Birimian greenstone. In Guinea, these formations are located in the Siguiri basin which covers the prefectures of Siguiri, Mandiana, Dinguiraye, Kankan and Kouroussa. In the region, significant gold deposits related to these formations are being mined and others are depleted. Despite the existence of a similar regional geological context, each of the deposits found in the West African craton has particular litho-geochemical, structural, textural or mineralogical characteristics. Which attests that in the sub-region, for the search for gold, litho-geochemical, structural and mineralogical studies are crucial. Thus, this study aims to identify the lithologies and alterations that control the Kourouba gold mineralization. To achieve this goal, we modeled the survey data and performed geochemical analyses with different diagrams. At the end of this study, we obtained that the Kourouba area has a lithology that presents itself from the surface to the depth as follows: Laterite, Baryonic clay, Saprolite clay and Mafic with an alternation of Cherts in certain areas. The geotectonic context that controls mineralization is of the active continental margin types with the presence of iron-rich schistose meta-sediments. Two (2) degrees of alteration have been identified, the mineralizations are filonial and disseminated in the mafic rocks.